Qualitative Approach in Research in the Discipline of Civic Education: Paradigms and Conceptions - hendra (Synergy: Journal of Collaborative Sciences, 2025)
Qualitative research, as research that focuses on the quality of a symptom or phenomenon, can be used in the development of the discipline of civic education. Qualitative research is used to solve various problems that are not rigid and described quantitatively, but still able to solve problems holistically and systematically. This article aims to discuss and examine the paradigm and concept of a qualitative approach in civic education. The article was written using a literature review. Data were collected by reviewing and analyzing various literature, books, journals, and research results relevant to the discussion. The data were analyzed using descriptive analysis. The results of the review indicate that the goal of civic education is to create good citizens, with the main study discussing humans and their behavior in national and state life. Its development requires a qualitative research approach. In addition, there are five approaches in qualitative research that can be used in research in the discipline of civic education: narrative, phenomenology, grounded theory, ethnography, and case studies.